2001
DOI: 10.1016/s0022-5096(00)00029-6
|View full text |Cite
|
Sign up to set email alerts
|

Slip dynamics at an interface between dissimilar materials

Abstract: It has been shown recently that steady frictional sliding along an interface between dissimilar elastic solids with Coulomb friction acting at the interface is ill-posed for a wide range of material parameters and friction coefficients. The ill-posedness is manifest in the unstable growth of interfacial disturbances of all wavelengths, with growth rate inversely proportional to the wavelength. We first establish the connection between the ill-posedness and the existence of a certain interfacial wave in frictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
272
2
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(291 citation statements)
references
References 19 publications
(36 reference statements)
15
272
2
2
Order By: Relevance
“…Cochard and Rice (2000) showed that the model which Andrews and Ben-Zion used, with constant friction coe cient, would not give numerical convergence with grid reÿnement, due to the ill-posedness discussed. Cochard and Rice (2000) also showed that a reformulation of the problem using the regularized friction law of Ranjith and Rice (2001) did lead to convergent solutions with properties somewhat like those suggested by Andrews and Ben-Zion (1997). Extensive further studies along those lines, using the same regularized friction law, are reported by Ben-Zion (2001).…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…Cochard and Rice (2000) showed that the model which Andrews and Ben-Zion used, with constant friction coe cient, would not give numerical convergence with grid reÿnement, due to the ill-posedness discussed. Cochard and Rice (2000) also showed that a reformulation of the problem using the regularized friction law of Ranjith and Rice (2001) did lead to convergent solutions with properties somewhat like those suggested by Andrews and Ben-Zion (1997). Extensive further studies along those lines, using the same regularized friction law, are reported by Ben-Zion (2001).…”
Section: Introductionmentioning
confidence: 63%
“…The problem of stability of steady sliding between dissimilar materials has received much recent attention in theoretical modeling (Renardy, 1992;Martins et al, 1992Adams, 1995;Martins and Simões, 1995;Simões and Martins, 1998;Cochard and Rice, 2000;Ranjith and Rice, 2001). That work has, mostly, neglected rate and state e ects, instead assuming a constant coe cient of friction f, and has focused on the coupling between inhomogeneous slip and alteration of normal stress.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Frictional resistance laws that range from the simplest Amontons-Coulomb stick-slip friction [17], to heuristic laws such as slip-or velocity-weakening laws [4,17,18], to laws based on recent laboratory friction experiments including rate-andstate [19][20][21][22][23][24][25][26][27][28] and leaky threshold laws [18,25,26,28], to other types of rupture and healing laws characterized by inner-and outer-physical scales [7].…”
Section: The Virtual California Modelmentioning
confidence: 99%